Goodbay is not Forever - George, Amy. (Eugene, Oregone Harvesr House Publishers, 1978)
One dark night, when Ame was only a baby, the Soviet secret police forcefully arrested Amys father...and condemned him to the frigid wastelands of Silberia. Then as World War II began, armies of the Third Reich invaded her small Russian village. Amy, a tender seven-year-old child, was taken by cattle car to a slave labor camp and witnessed forsthand the horrors of Hitlers Germany.
Keywords: Literature